Donor funding health policy and systems research in low- and middle-income countries: how much, from where and to whom - Karen Ann Grépin; Crossley Beth Pinkstaff; Zubin Cyrus Shroff; Abdul Ghaffar (BMC, 2017)
Abstract Background The need for sufficient and reliable funding to support health policy and systems research (HPSR) in low- and middle-income countries (LMICs) has been widely recognised. Currently, most resources to support such activities come from traditional development assistance for health (DAH) donors; however, few studies have examined the levels, trends, sources and national recipients of such support - a gap this research seeks to address. Method Using OECD's Creditor Reporting System database, we classified donor funding commitments using a keyword analysis of the project-level descriptions of donor supported projects to estimate total funding available for HPSR-related activities annually from bilateral and multilateral donors, as well as the Bill and Melinda Gates Foundation, to LMICs over the period 2000-2014. Results Total commitments to HPSR-related activities have greatly increased since 2000, peaked in 2010, and have held steady since 2011. Over the entire study period (2000-2014), donors committed a total of $4 billion in funding for HPSR-related activities or an average of $266 million a year. Over the last 5 years (2010-2014), donors committed an average of $434 million a year to HPSR-related activities. Funding for HPSR is heavily concentrated, with more than 93% coming from just 10 donors and only represents approximately 2% of all donor funding for health and population projects. Countries in the sub-Saharan African region are the major recipients of HPSR funding. Conclusion Funding for HPSR-related activities has generally increased over the study period; however, donor support to such activities represents only a small proportion of total DAH and has not grown in recent years. Donors should consider increasing the proportion of funds they allocate to support HPSR activities in order to further build the evidence base on how to build stronger health systems.